External quality control program in infectious diseases screening at laboratories and blood banks in Latin America: an analysis of the past 5 years - Alfredo Mendrone-Junior; Nanci Salles; Marcia Otani; Adenilson Countinho; Lucas Bassolli de Oliveira Alves; Vanderson Rocha; Mauricio Beltrán-Durán (Pan American Health Organization, 2023)
Objective. To evaluate the screening of blood samples for infectious disease markers at laboratories and blood banks in Latin America per the findings of an External Quality Assessment Program (EQAP). Methods. This qualitative analysis used data from the EQAP coordinated by the Fundação Pro Sangue Hemocentro de São Paulo with the support of the Pan American Health Organization to assess the performance of blood screening for infectious diseases from 2014 to 2018 in Latin America. Each participating laboratory or blood bank received an identical blind panel with 24 blood samples with variable reactivity for all the screening parameters. Panels were processed at each participating facility and results were returned to the Fundação Pro Sangue Hemocentro de São Paulo for individual and joint analyses. Two types of discrepant results were potential failures: false positive results (FPRs) and false nonreactive results (FNRRs). Results. A total of 23 136 samples were evaluated. Global rates of FPR, FNRR, and concordant results were 0.3%, 1.0% and 98.7%, respectively. Seven FNRRs were found for HBsAg (1.0%), 12 for syphilis (2.6%), and 21 for Chagas disease (2.9%). No FNRRs were found for the HIV, HCV, and HTLV viruses. The average accuracy of all the laboratories and blood banks participating in the EQAP during the study period was 99.5% (standard deviation, 0.5%). Conclusion. The findings of this qualitative analysis are positive for blood safety in Latin America, with an average accuracy of 99.5% among the participating laboratories and blood banks. This report reflects an important improvement in blood bank serological screening EQAP-PAHO report since the 2003.